Do we care about going green? Measuring the effect of green environmental awareness, green product value and environmental attitude on green culture. An insight from Nigeria - Ogiemwonyi, Osarodion; Harun, Amran; ALAM, Mohammad Nurul; Othman, Bestoon Abdulmaged (Sciendo, 2020)
As the environment continues to aggravate, it has become a purposeful public concern in developed countries and has recently stirred developing countries to join the green movement. Hence, this study examines green environmental awareness, green product value and environmental attitude by applying the measurement of effects on green culture. The study applied a quantitative research approach where a cross-sectional survey designed with 267 respondents’ green consumer who lived in the urban area of Abuja and employed partial least squares structural equation modelling (PLS-SEM) using SmartPLS3 to examine the developed path model. The results indicated that all constructs were empirically supported showing significant impact on green culture while examining direct relationships. The resulting (Q2) value is larger than zero (0) in the path model, this specifies that exogenous constructs have a good index for predictive relevance on the endogenous construct being investigated. Among the construct, awareness is the most important predictor and green product value tends to show a modest impact on environmental attitude. The study suggests that policymakers should place emphasis on environmental values to boost environmental awareness among young consumers in the process of making purchases. Specifically, environmental attitude was found to have full mediation on the relationship between green product value and green culture. However, no mediation occurs in the relationship between environmental awareness and green culture. The study concluded that awareness regarding going green activism in Nigeria among young consumers is still a matter of concern despite its impact and therefore, practitioners and collaborators in the green industry need to apply aggressive efforts to achieve this pathway, to ensure the design and implementation of effective policies that will promote going green and enhance the green circular economy.